Increasing Purchase Intention Through Trust, Social Media Marketing, and Brand Image for Furniture Products in Jepara - Abelia Jenita Pricia; Alifah Ratnawati (Komunitas Dosen Indonesia, 2026)
Developments in digital marketing have encouraged furniture entrepreneurs in Jepara to utilize social media platforms as promotional tools in responding to increasingly intense market competition. Nevertheless, fluctuations in Jepara furniture sales and export performance indicate that digital marketing efforts have not yet achieved optimal outcomes. This study aims to examine the effect of social media marketing and brand image on purchase intention, with trust positioned as an intervening variable in the context of Jepara furniture products. A quantitative approach was employed using a survey method by distributing structured questionnaires to 204 respondents who had viewed or searched for information related to Jepara furniture products through social media platforms. Purposive sampling was applied, while data were analysed using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) technique. The findings reveal that social media marketing and brand image have a positive and significant influence on consumer trust. Furthermore, trust, social media marketing, and brand image are proven to have a positive and significant impact on purchase intention, highlighting the critical role of trust in strengthening digital marketing effectiveness.